Work And Leisure: A Study of Social Tourism in Higher Education Institutions in Bali - Yayu Indrawati; Putu Sucita Yanthy; I Wayan Darsana Darsana; I Putu Andre Adi Putra Pratama (Postgraduate, University of Mataram, 2024)
This study examines social tourism within higher education institutions in Bali, Indonesia, using an inclusive approach that involved both lecturers and students from public and private universities. Employing a mixed-methods design, the research collected quantitative data through surveys distributed across five universities in Bali Province, while qualitative data was obtained from interviews with participants knowledgeable about inclusive social tourism. The findings reveal that social tourism activities are integrated with the Tri Dharma of Higher Education, emphasizing teaching, research, and community service. These activities blend academic endeavors, such as field research, workshops, seminars, and benchmarking, with tourism experiences like sightseeing and cultural events. The study highlights the benefits of social tourism for the academic community, including increased social capital, improved self-confidence, and enhanced knowledge and skills. Additionally, social tourism fosters collaboration between universities and contributes to the mental and physical well-being of academics, helping to alleviate burnout. The study suggests that higher education institutions should consider policies that leverage social tourism to enhance academic experiences and promote holistic development among faculty and students.